2021
DOI: 10.15407/zoo2021.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Can You Hear Me Now? A Comparative Survey of Pinniped Auditory Apparatus Morphology

Abstract: Over the past century research on the morphology of the auditory apparatuses of pinnipeds, which include Phocidae (true seals), Otariidae (sea lions and fur seals), and Odobenidae (walruses) is extremely limited, in comparison to other Carnivora. Although, the auditory region and surrounding basicrania are areas that are evolutionarily conservative, most literature is unclear due to mixed terminology, inaccurate information, and indistinct, outdated illustrations. Th e lack of adequate and current studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 61 publications
(193 reference statements)
0
11
0
Order By: Relevance
“…One of the major unresolved issues with current auditory research is how Phocidae (true seals), Otariidae (fur seals and sea lions), and Odobenidae (walruses) hear efficiently in both aquatic and terrestrial environments (Kastak & Schusterman, 1998; Reichmuth et al, 2013; Repenning, 1972; Smodlaka et al, 2018). Current auditory research focuses more on behavior, determining that pinnipeds can hear moderately well on land (about as well as humans), with otariids having the best aerial acuity, and that all pinnipeds hear at significantly higher frequencies (phocids having the best results) in the water (Ghoul & Reichmuth, 2014; Koper et al, 2021; Reichmuth et al, 2013). Audiogram results demonstrate that two completely different hearing mechanisms should be present, one for each environment, but the specific morphology of pinniped auditory apparatuses has still not been thoroughly explored (Koper et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the major unresolved issues with current auditory research is how Phocidae (true seals), Otariidae (fur seals and sea lions), and Odobenidae (walruses) hear efficiently in both aquatic and terrestrial environments (Kastak & Schusterman, 1998; Reichmuth et al, 2013; Repenning, 1972; Smodlaka et al, 2018). Current auditory research focuses more on behavior, determining that pinnipeds can hear moderately well on land (about as well as humans), with otariids having the best aerial acuity, and that all pinnipeds hear at significantly higher frequencies (phocids having the best results) in the water (Ghoul & Reichmuth, 2014; Koper et al, 2021; Reichmuth et al, 2013). Audiogram results demonstrate that two completely different hearing mechanisms should be present, one for each environment, but the specific morphology of pinniped auditory apparatuses has still not been thoroughly explored (Koper et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Smodlaka et al (2018) hypothesized that specialized diving adaptations seen in Mirounga angustirostris (northern elephant seal) do not allow for efficient aerial hearing through the external ear, and so this pinniped may depend instead on seismic vibrations through bone conduction. Beyond these hypotheses, there have been no other current studies into the mechanisms pinnipeds employ to hear efficiently inside and outside of the water (Koper et al, 2021; Smodlaka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the relationship between the morphology of components of the auditory apparatus, such as the middle ear ossicles, cochlea, and bony labyrinth, and ecology has been studied before in numerous species (Bhagat et al, 2020;Kerber & Sánchez-Villagra, 2018;Mason, 2001Mason, , 2016Mason et al, 2010;Pfaff et al, 2015;Pleštilová et al, 2021). Tympanic bullar morphology itself has been investigated in specific species of mammals (Basso et al, 2017;Groves et al, 2021;Koper et al, 2021), including rodents (Alhajeri et al, 2015;Momtazi et al, 2008;Pleštilová et al, 2021;Potapova, 2019;Schleich & Vassallo, 2003;Tabatabaei Yazdi et al, 2014;Zherebtsova & Potapova, 2019) and has been shown to be associated with habitat use. In particular, inflated tympanic bullae and the associated sound amplification have been linked to open and arid environments (Alhajeri et al, 2015;Tabatabaei Yazdi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%